Event Marketing sebagai Upaya untuk Memaksimalkan Akuisisi Pelanggan: Studi Kasus pada Perusahaan E-commerce X - Mulawarman, Logi; Palit, Juliana; ., Darusalam (Universitas Bumigora, 2023)
Event marketing activities involve the use of a certain time, layout, management, and the participation of various parties. Event marketing is a strategy to introduce products and attract customers. The purpose of this study is to explain event marketing strategies to maximize customer acquisition in e-commerce X. Qualitative research with case studies has been implemented in one of the e-commerce in Indonesia. Interviews were conducted with five informants who were employees at the City Y Branch Office. The results showed that the form of event marketing from e-commerce X was divided into two activities, namely offline events and online events. Offline and online event marketing activities basically have the same form of events including roadshows, bazaars, seminars, and sponsoring other activities. Marketing events are held in schools or strategic places. The impact of the event marketing strategy carried out by e-commerce X has been positive on customer acquisition. The company's success in acquiring customers can be seen from the fulfillment of targets set by the company.